Investigating the Usefulness of a New Electronic Error- Reporting System in Medical Error Management in the Shohadaye Haftom Tir Hospital in 2019-2020 - Shirin Nasrolahnejhad Tasouj; Fatemeh Mohammadi; Mehdi Nouri; Reza Mosaddegh; Samira Vaziri (Patient Safety and Quality Improvement Journal, 2022)
Introduction:Providing health services in medical centers is associated with risks and medical errors for recipients. In many cases, despite medical experts’ ethical and professional commitment to disclose errors, the error report among treatment staff is less than the actual rate. Therefore,, the present study was conducted to investigate using a new electronic error-reporting registration system method in Shohadaye Haftom Tir Hospital in 2018-2019. Materials and Methods: This was a descriptive cross-sectional study. Errors reported in 2018 and 2019 were investigated using the paper-based method and electronic error-reporting system, respectively. Data were analyzed using SPSS software (version 22) after classifying errors.  Results: In the electronic method, 194 errors were reported, of which medication errors accounted for 33% and medical errors for 22% of the total errors. Hospital congestion was one of the major causes of the error. Nurses were more likely to make medical errors than other groups. In the paper-based reporting error method, out of 44 cases, about 37% were technical-related errors. The most important cause of the error was a lack of proper communication with the patient (30%). Findings suggested that the error percentage significantly increases in both methods due to the causes, specific sectors, and job categories. Conclusion:Findings have shown the efficiency of the electronic system in detecting errors. Managers` attention and actions toward using the electronic system can greatly affect the health and treatment of patients.